Liability for third-party harm when harm-inflicting consumers are present biased - Tim Friehe; Christoph Rössler; Xiaoge Dong (University of Hamburg, Institute of Law and Economics (ILE), 2018)
This paper analyzes the workings of liability when harm-inflicting consumers are present biased and both product safety and consumer care influence expected harm. We show that present bias introduces a rationale for shifting some losses onto the manufacturer, in stark contrast with the baseline scenario in which strict consumer liability induces socially optimal product safety and precaution levels. In addition, we establish that strict liability with contributory negligence may induce socially optimal product safety and precaution choices without aggravating the output level distortion.
Keywords: D91; H23; K13; 330; Liability; Present Bias; Product Safety; Consumer Precaution